Diagnostic impact of ascites cytology in 941 patients: malignancy rates and time of detection in ovarian cancer relative to other tumor types - Krugmann, Jens; Schwarz, Corinna Lang; Melcher, Balint; Sterlacci, William; Rösch, Sophia; Lermann, Johannes; Vieth, Michael (Archives of Gynecology and Obstetrics, 2020)
Background: Cytological analysis of ascitic fluid is an important tool for diagnosis, staging, and prognostic assessment in patients with cancer, but more detailed information is needed regarding malignancy rates and the time sequence in which ascites develops for different sites of cancer origin. Especially, an increased early tumor diagnosis may improve the acceptance for cytological examinations for the tumor patients in oncological practice. Methods: Ascites specimens from patients who were treated at Bayreuth Hospital from 2006 to 2015 were reevaluated retrospectively and correlated with clinical reports. Results: 580 of all 941 ascitis specimens (61.6%) were from patients with malignancies with predominant appearance of gastrointestinal and gynecological tumors in 516/580 (89%) patients. Histologically, 549 (94.6%) were carcinomas, 23 (4%) hematological malignancies, 5 (0.9%) mesotheliomas and 3 (0.5%) were melanomas. Malignant ascitic fluid was noted in 298 of the 580 (51.4%) patients with cancer, thus the overall malignancy rate in the ascites specimens examined was 298/941 (31.7%). The most frequent malignancy rate for gynecological tumors we obtained in ovarian cancer with 85.7% and in the upper gastrointestinal tract with 77.8% for Barrett’s carcinoma and 61,4% for gastric carcinoma. Regarding time of detection, malignant ascitic fluid was noted as a separate finding, prior or simultaneous to the histological diagnosis of cancer in 225/298 patients (75.5%). An outstanding earliest occurrence was found in ovarian carcinoma in 94.9% and in the gastrointestinal tract in pancreatic carcinoma in 66.7%. Conclusions: Tumor staging was the main important clinical question in our single center study of ascitic fluid, especially for patients with gastrointestinal and gynecological malignomas. The highest malignancy rate and earliest time of tumor detection caused the leading importance for ovarian tumors in malignant ascitic fluid. Moreover, the application of immunostains in our study allowed in 75.5% of all tumor patients a correct initial diagnosis, which is important for further clinical therapy.
CRIS-Team Scopus Importer:2020-05-08
Keywords: Malignancy rates; Malignant ascites; Neoplasia; Time of detection